Predicting the revolving door phenomenon among patients with schizophrenic, affective disorders and non-organic psychoses Fatores preditores do fenômeno de reinternações de pacientes esquizofrênicos, com transtorno afetivo e psicose não orgânica - Fábio L Gastal; Sérgio B Andreoli; Maria Inês S Quintana; Maurício Almeida Gameiro; Sérgio O Leite; John McGrath (Universidade de São Paulo, 2000)
OBJECTIVE: The aim of the study was to identify the variables that predict the revolving door phenomenon in psychiatric hospital at the moment of a second admission. METHODS: The sample consisted of 3,093 patients who have been followed during 5 to 24 years after their first hospital admission due to schizophrenia, and affective or psychotic disorders. Those who had had four or more admissions during the study period were considered as revolving door patients. Logistic regression analyses were used to assess the impact of gender, age, marital status, urban conditions, diagnosis, mean period of stay on the first admission, interval between the first and second admissions on the patterns of hospitalization. RESULTS: The variables with the highest predictive power for readmission were the interval between first and second admissions, and the length of stay in the first admission. CONCLUSIONS: These data may help public health planners in providing optimal care to a small group of patients with more effective utilization of the available services. OBJETIVO: Identificar as variáveis preditoras do fenômeno de reinternações (recidividade) em hospital psiquiátrico no momento da segunda internação. MÉTODOS: A amostra consistiu em 3.093 pacientes com diagnósticos de esquizofrenia, transtorno afetivo e psicose não orgânica acompanhados durante um período de, no mínimo, 5 anos e, no máximo, 24 anos. Foram considerados pacientes recidivistas os que tiveram 4 ou mais internações no período do estudo. Foi utilizado o modelo de regressão logística para análise do impacto das variáveis sexo, idade, estado civil, cidade de residência, diagnóstico, tempo de permanência na primeira internação, tempo entre a primeira e a segunda internação, segundo o padrão de re-hospitalização. RESULTADOS: As variáveis com maior poder de predição foram tempo entre a primeira e a segunda internação, tempo de permanência na primeira internação e diagnóstico de esquizofrenia. CONCLUSÕES: Os resultados são importantes para o planejamento de saúde pública, com o intuito de promover melhores cuidados a um grupo de pacientes pequeno, mas com um alto impacto na utilização do serviço.